Blood Pressure and Penumbral Sustenance in Stroke from Large Vessel Occlusion - Regenhardt, Robert W.; Das, Alvin S.; Stapleton, Christopher J.; Chandra, Ronil V.; Rabinov, James D.; Patel, Aman B.; Hirsch, Joshua A.; Leslie-Mazwi, Thabele M. (Frontiers in Neurology, 2017)
The global burden of stroke remains high, and of the various subtypes of stroke, large vessel occlusions account for the largest proportion of stroke-related death and disability. Several randomized controlled trials in 2015 changed the landscape of stroke care worldwide, with endovascular thrombectomy now the standard of care for all eligible patients. With the proven success of this therapy, there is a renewed focus on penumbral sustenance. In this review, we describe the ischemic penumbra, collateral circulation, autoregulation, and imaging assessment of the penumbra. Blood pressure goals in acute stroke remain controversial and we review the current data and suggest an approach for induced hypertension in the acute treatment of patients with large vessel occlusions. Finally, in addition to reperfusion and enhanced perfusion, efforts focused on developing therapeutic targets that afford neuroprotection and augment neural repair will gain increasing importance. Endovascular thrombectomy has revolutionized stroke care, and future emphasis will be placed on promoting penumbral sustenance, which will increase patient eligibility for this highly effective therapy, and reduce overall stroke-related death and disability.